Pemodelan Dampak Perubahan Iklim dan WIUP terhadap Potensi Habitat Burung Walik Benjol di Pulau Obi - Kartika Pratiwi; Supriatna Supriatna; Masita Dwi Mandini Manessa; Aris Poniman K; Mangapul P. Tambunan (Fakultas Teknik, 2023)
AbstractOne of the impacts of climate change is the degradation quality of natural habitats of flora and fauna in Indonesia, risking the loss of most of the existing biodiversity. Obi Island as a natural habitat for several endemic species cannot be avoided from the threat of climate change impacts. The existence of mining concessions also can have a direct impact on their habitat potential. The purpose of this study was to analyze the distribution pattern of endemic species under current climatic conditions, synthesize models of the impact of climate change and analyze mining concessions on the distribution of potential habitats of Carunculated Fruit-dove on Obi Island. The occurrence data of Carunculated Fruit-dove and 19 bioclimatic variables are used as input in the process of making a habitat model with MaxEnt. As a result, the habitat potential model of Carunculated Fruit-dove with AUC = 0.955 has a very suitable habitat potential with an area of 66.02 km2 or 2.68%. The climate change in 2041-2060 with 4 different climate scenarios has an impact on the Carunculated Fruit-dove habitat potential model. Mining Business Permit Areas on Obi Island that have been issued until March 2022 amount to 19 locations with a total area of 373.14 km2 which will have a direct or indirect impact on the potential habitat of Carunculated Fruit-dove on Obi Island. 14.17 km2 of 66.67 km2 of potential habitat that is very suitable for Carunculated Fruit-dove will be directly affected by the existence of these mining areas.Keywords: endemic species, mining business permit area, climate change, obi island, maximum entropy